درجة ممارسة مديري مدارس التعليم الأساسي / ح 1 للدعم النفسي الاجتماعي (Journal of Hama University, 2023)
The research aims to identify the degree of principals' practice of basic education/H1 schools for psychosocial support from their point of view in the Salmiya area, and to identify the differences between the degrees of the sample members on the psychosocial support scale according to the variables (gender, educational qualification, years of experience). The research sample consisted of (103) male and female managers, and the research relied on the descriptive approach, and the psychosocial support scale was applied, designed by the researcher, as a research tool, so that it consisted of (29) phrases. The results of the research confirmed that the degree of principals of basic education/H1 schools practicing psychosocial support was high, with statistically significant differences between the mean scores of the research sample on the psychosocial support scale according to the gender variable in favor of males, and the variable of years of experience in favor of the category (from 6- 10 years), and the educational qualification variable in favor of the institute and university degree holders. In the light of these results, the researcher recommended conducting studies on psychosocial support in the school, and adopting the responsible authorities a set of laws that take into account (years of experience, educational qualification and gender) while selecting principals for basic education schools / H1 with the implementation of tests that allow measuring the principal's knowledge and understanding of his tasks in psychological support social; Including it as a course for psychosocial support within all specializations of the faculties of education.